2022
DOI: 10.1097/hjh.0000000000003226
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker screening in preeclampsia: an RNA-sequencing approach based on data from multiple studies

Abstract: Objective:Biomarkers have become important in the prognosis and diagnosis of various diseases. High-throughput methods, such as RNA sequencing facilitate the detection of differentially expressed genes (DEGs), hence potential biomarker candidates. Individual studies suggest long lists of DEGs, hampering the identification of clinically relevant ones. Concerning preeclampsia – a major obstetric burden with high risk for adverse maternal and/or neonatal outcomes – limitations in diagnosis and prediction are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Fibronectin 1 (FN1) is a glycoprotein that is involved in cell adhesion and cell spreading and is widely distributed in healthy membranes, vascular structures, and smooth muscle cell layers. [25][26][27] The plasma levels of FN1, which may be the best marker for vascular endothelial injury during PE, are increased in patients with PE. [28] Multiple studies have shown that FN1 is related to the pathogenesis of PE, and FN1 can be used as a potential marker in the diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin 1 (FN1) is a glycoprotein that is involved in cell adhesion and cell spreading and is widely distributed in healthy membranes, vascular structures, and smooth muscle cell layers. [25][26][27] The plasma levels of FN1, which may be the best marker for vascular endothelial injury during PE, are increased in patients with PE. [28] Multiple studies have shown that FN1 is related to the pathogenesis of PE, and FN1 can be used as a potential marker in the diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to heavy metals like lead and cadmium can antagonize mineral absorption and function, potentially worsening fertility challenges [6]. While the influence of minerals on male fertility has been intensively investigated [7][8][9][10], their role in women's reproductive health and menstrual cycle has been marginally addressed, often only in the context of specific reproductive pathologies [11,12], emphasizing vitamins and multivitamin supplementation. Notably, these studies frequently lack in-depth investigation of the role of minerals and the underlying mechanisms, neglecting the phases of the menstrual cycle [13].…”
Section: Introductionmentioning
confidence: 99%